Multiuser diversity scheme with partial feedback of channel metric on common uplink channel and its performance - GONG Ming; QIU Ling; ZHU Jin-kang (Tongxin xuebao)
By investigating the throughput performance of multiuser diversity system with random beamforming, a multiuser diversity scheme with partial feedback of channel metric on common uplink channel were proposed. Performance analysis proves that with proper threshold, partial feedback of channel quality can pay much less for uplink feedback with little decrease of system throughput, which means that the system will accommodate more user within given bandwidth.